Early recognition of possible pitfalls in histological diagnosis of celiac disease. (September 2015) - Eigner, Wolfgang; Wrba, Friedrich; Chott, Andreas; Bashir, Kerstin; Primas, Christian; Eser, Alexander; Vogelsang, Harald
Abstract Objective. A state-of-the-art assessment of duodenal biopsies by the pathologist in the diagnosis of celiac disease (CelD) is of highest importance. However, inaccurate characterization of specific features can lead to misdiagnosis. Our hypothesis is that a detailed histological report guarantees a good quality and helps in the primary diagnostic process by preventing false-positive diagnosis of CelD. Material and methods. A total of 52 patients primarily diagnosed with CelD and suspicion of misdiagnosis were selected for this retrospective study. External histological reports of duodenal biopsies were obtained and later reassessed by an experienced in-house pathologist. For an objective evaluation a histology quality score (HQS) was created. Both pathological reports were compared and causes for a possible misdiagnosis were analyzed. Diagnostic systems by Catassi and Korponay-Szabo were compared with each other. Results. The original diagnosis had been confirmed in 27% by our pathologist. The HQS was significantly lower (worse) in cases where the original diagnosis were dismissed than in confirmed CelD (p = 0.018). The new diagnostic approach by Catassi and Korponay-Szabo showed a sensitivity of 89% and 83%, respectively, a specificity of 97%, a positive predictive value of 94% and a negative predictive value of 94% and 92%, respectively. Conclusions. A low quality of the histological evaluation can lead to a high probability of misdiagnosing CelD. By applying the HQS the physician can estimate whether the report is fraught with uncertainty. Ideally the score minimizes false-positive results and prevents a delay of the correct diagnosis.